Overview of case law of the European Court of Human Rights on wearing religious clothes and religious symbols (International relations and international law Journal, 2017)
The European Court of Human Rights is one of the most authoritative international judicial bodies, having a huge case-law in the field of protection of human rights. The decisions presented in this article contain the legal position of the Court in matters of wearing religious clothes and religious symbols, representing the next stage in the development of international law model of human rights. The decisions rendered by Court, are legally obligatory only for the respondent States, however in view of practice, often the importance of decisions of the European Court goes beyond national framework, thus affecting the law and jurisprudence of other States. Considering the specificity of the existing difficulty of resolving similar problems in the Republic of Kazakhstan, the authors believe that «the examined cases» will contribute to the integration of the legal system of the State.
Keywords: freedom of religion; religious clothes; symbols; the Court; complaint